Genome-based analysis of the family Paracoccaceae and description of Ostreiculturibacter nitratireducens gen. nov., sp. nov., isolated from an oyster farm on a tidal flat - Huang, Zhaobin; Li, Meiqin; Oren, Aharon; Lai, Qiliang (Frontiers in Microbiology, 2024)
Two bacterial strains, designated FR2A1T and MT2-5-38, were isolated from the surface sediments of an oyster farm on a tidal flat in Quanzhou Bay, China. Both strains were Gram-stain-negative, rod-shaped, aerobic, catalase-positive, and oxidase-positive. The 16S rRNA gene sequences of the two strains were 100% identical and had the highest similarity (97.1%) with Phaeovulum vinaykumarii JA123T. The average nucleotide identity (ANI) value and digital DNA–DNA hybridization (DDH) value indicated that the two strains belonged to a single species. Gene annotation revealed that the two strains contained a gene cluster for nitrate reduction and a gene cluster for sulfur oxidation, indicating a possible role in N and S cycling in the tidal flat sediment. The phylogeny inferred from the 16S rRNA gene and 120 conserved proteins indicated that the two strains formed a distinct monophyletic clade within the family Paracoccaceae. The respiratory quinone was Q-10. The major fatty acids consisted of summed feature 8 (C18:1ω7c and/or C18:1ω6c) and C18:0. The polar lipids consisted of phosphatidylethanolamine, phosphatidylglycerol, and several unidentified phospholipids. Based on the above characteristics, strains FR2A1T and MT2-5-38 represent a novel genus and a novel species, for which we propose the name Ostreiculturibacter nitratireducens gen. nov., sp. nov. The type strain is FR2A1T (=MCCC 1K08809T = KCTC 8317T). Phylogenomic analysis of 1,606 high-quality genomes of the family Paracoccaceae, including type strains, non-type strains, and uncultivated bacteria, was performed using the Genome Taxonomic Database Toolkit (GTDB-Tk), and the average amino acid identity (AAI) value of the phylogenetic clade was estimated. We found that 35 species of the family Paracoccaceae needed re-classification, and an AAI value of 70% was chosen as the genus boundary within the family Paracoccaceae.